The Family Support in Strengthening Fine Motor Ability for Children 3-4 Years Old - Ludyanti, Laviana; Hayati, Farida; Fuadah, Dina Zakiyyatul (Journal of Applied Nursing and Health, 2023)
Background: Family was the first school for children to support their growth and development. Fine motor development of children 3-4 years old can develop optimally if they get optimal family support through good and correct stimulation.  This research to determine the relationship between family support and fine motoric skills in children aged 3-4 years at the Smart Kids Preschool. Methods: The design of this study was correlational with a cross sectional approach using a questionnaire. The independent variable is family support and the dependent variable is fine motoric skills in children aged 3-4 years, with a population and sample consisting of 35 respondents using total sampling. The research data were analyzed using the Spearman Rank Test. Results: The results of the family support study showed that almost all respondents (82.9%) were in good criteria, in the fine motoric skills of children aged 3-4 years, almost all of them (85.7%) were in the appropriate criteria. The results of data analysis showed p-value = 0.000 (α = 0.05) with a correlation level of 0.703 which means there is a strong relationship between family support and fine motoric skills of children aged 3-4 years. This is influenced by many factors, one of which is internal factors and external factors such as motivation to practice, health, motivation or attributes that distinguish a person from others, then parental knowledge, parental education, parental attitudes, socio-economic family, socio-cultural, environment, and parenting.  Conclusion: Based on the result of this study, it is suggested that mothers can provide stimulation so that the potential of children can develop optimally by providing optimal support for children.